The Effect of Personality on Decision Making - Jalajas, David S.; Pullaro, Ray (Journal of Organizational Psychology, 2018)
This study examines whether personality can predict error making in decisions made using heuristics. We predicted that certain personalities would be more likely to use heuristics and therefore lead to more errors. We measured the personality of college students with the Big Five Inventory, and measured decision making through six decisions. Using a set of binary logistic regression models, we found that Conscientiousness was unexpectedly negatively related to correct decisions, and Agreeableness and Neuroticism had expectedly negative relationships with correct decisions. Openness was negatively related to correct decisions. An explanation for these findings is presented.